Preparation method and application of negative electrode coating material of aqueous zinc ion battery

By loading enzymatic lignin on graphite phase carbon nitride, enzymatic lignin graphite phase carbon nitride composite material is prepared, which solves the negative electrode corrosion and dendrites of aqueous zinc ion batteries, and significantly improves the stability of the battery and Cyclic efficiency.

CN119400795AActive Publication Date: 2025-02-07DALIAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411529896.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The negative electrode of the aqueous zinc ion battery has problems such as dendrite growth, hydrogen evolution, surface corrosion and by-product formation, which hinders its commercial application.

Method used

By loading enzymatic lignin on graphite phase carbon nitride, an enzymatic lignin graphite phase carbon nitride composite was prepared as the negative electrode coating material for aqueous zinc ion batteries, which was used to inhibit the corrosion of zinc negative electrode and dendrite reaction.

Benefits of technology

It effectively suppresses the corrosion of the zinc negative electrode surface by the electrolyte, and improves the circulation stability and charge and discharge cycle efficiency of the aqueous zinc ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005110227500000011
    Figure HDA0005110227500000011
  • Figure HDA0005110227500000012
    Figure HDA0005110227500000012
  • Figure HDA0005110227500000013
    Figure HDA0005110227500000013
Patent Text Reader

Abstract

The invention belongs to the technical field of aqueous zinc ion battery negative electrode materials, and discloses a preparation method and application of a negative electrode coating material of an aqueous zinc ion battery. The graphite phase carbon nitride is adopted as a base material, the enzymatic hydrolysis lignin is loaded in the graphite phase carbon nitride to synthesize the enzymatic hydrolysis lignin graphite phase carbon nitride composite material, and the synthesized material not only has relatively high mechanical property and chemical stability, but also can effectively inhibit the corrosion of electrolyte to the surface of a zinc negative electrode. The required zinc negative electrode coating material is prepared by loading the enzymatic hydrolysis lignin on the graphite phase carbon nitride. The coating material is used as a protective layer of the water-based zinc ion battery negative electrode material, can solve the problems generated in the charging and discharging process of the zinc ion battery negative electrode, inhibits hydrogen evolution, corrosion, side reaction and dendritic crystals of the zinc negative electrode, and effectively improves the stability and the charging and discharging cycle efficiency of the water-based zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for aqueous zinc ion batteries, and the present invention relates to a preparation method and application of a negative electrode coating material for aqueous zinc ion batteries. Specifically, a composite material of graphite phase carbon nitride loaded with enzymatic lignin is used as a negative electrode coating material for aqueous zinc ion batteries, and the composite material is applied to the preparation of negative electrode materials for aqueous zinc ion batteries. Background Art

[0002] The rapid development of wearable electronics and electric vehicles has stimulated the growing demand for exploring new energy storage systems. However, lithium-ion batteries have limited energy density and potential safety issues with organic electrolytes. Aqueous multivalent ion batteries have great prospects due to their high energy supply through multiple electron transfer and the use of aqueous electrolytes. Among the main metals, Zn has a theoretical specific capacity of 5855 mAh cm -3 ) exceeds the theoretical specific capacity of lithium metal (2061 mAh cm -3 ). In addition, Zn has a high redox potential (-0.76 V relative to standard hydrogen electrode), which enables it to operate in aqueous electrolytes with higher ionic conductivity than organic electrolytes, which will ultimately lead to a significant rate performance. Other advantages of Zn also involve non-flammability, low cost and high safety, all of which are particularly beneficial for practical wearable technologies. Although significant progress has been made in the exploration of zinc storage materials and devices so far, some problems have hindered the commercial application of aqueous zinc-ion batteries, mainly the problems of dendrite growth, hydrogen evolution, surface corrosion and by-product formation at the negative electrode.

[0003] At present, most studies have applied lignin sulfonate in various fields, for example, sodium lignin sulfonate is used in electrolyte additives. Enzymatic lignin may be slightly soluble in electrolyte and cannot be directly applied as a coating on the surface of zinc foil; in previous studies, graphite phase carbon nitride was used directly as a coating to modify the zinc negative electrode of aqueous zinc ion batteries, but graphite phase carbon nitride cannot effectively inhibit the corrosion of the electrolyte on the surface of the zinc negative electrode, and the battery cycle charge and discharge effect is poor. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a negative electrode coating material of an aqueous zinc ion battery and its application, aiming at the growth, hydrogen evolution, corrosion and other problems of zinc negative electrode dendrites. The enzymatically hydrolyzed lignin is loaded on graphite phase carbon nitride to prepare the required zinc negative electrode coating material. The coating material, as a protective layer of the negative electrode material of the aqueous zinc ion battery, can solve the problems generated by the negative electrode of the zinc ion battery during the charging and discharging process, inhibit the occurrence of hydrogen evolution, corrosion, side reactions and dendrites at the zinc negative electrode, and effectively improve the stability and charging and discharging cycle efficiency of the aqueous zinc ion battery.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a negative electrode coating material for an aqueous zinc ion battery comprises the following steps:

[0007] (1) Using urea as a raw material, a light yellow solid powder is obtained by heat treatment;

[0008] (2) Light yellow solid powder, enzymatic lignin and polyvinylidene fluoride (PVDF) are ball-milled and mixed according to a mass ratio, and N-methylpyrrolidone (NMP) is added dropwise and stirred until the mixture becomes a coating state; thereby obtaining a negative electrode coating material.

[0009] Furthermore, in step (1), urea is placed in a crucible and heat treated in a muffle furnace, and the heat treatment conditions are: heating rate 4-5°C / min, calcination temperature 500-600°C, and calcination time 2-3 hours.

[0010] Furthermore, in step (2), graphite phase carbon nitride, enzymatic lignin and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 1-5:1:1, the ball milling mixing speed is 600-650r / min, the time is 30-60min, and 5-7 drops of N-methylpyrrolidone (NMP) are added.

[0011] Preferably, in step (1), urea is placed in a crucible and heat treated in a muffle furnace, and the heat treatment conditions are: heating rate 4.6° C. / min, calcination temperature 550° C., and calcination time 2 hours.

[0012] Preferably, in step (2), graphite phase carbon nitride, enzymatically hydrolyzed lignin and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 5:1:1, and the ball milling time is 30 minutes.

[0013] Enzymatic lignin is preferably purchased from Shandong Longli Group.

[0014] The present invention also seeks to protect the use of the negative electrode coating material prepared by the above preparation method in preparing zinc negative electrode materials, specifically: using a coating machine to coat the coating material on zinc foil to prepare the zinc negative electrode material.

[0015] The present invention adopts graphite phase carbon nitride as a matrix material, loads enzymatic lignin in the graphite phase carbon nitride to synthesize an enzymatic lignin graphite phase carbon nitride composite material, and the synthesized material not only has strong mechanical properties and chemical stability, but also can effectively inhibit the corrosion of the electrolyte on the zinc negative electrode surface.

[0016] The beneficial effects of the present invention compared with the prior art are:

[0017] (1) The present invention uses graphite phase carbon nitride as a matrix to load enzymatic lignin to synthesize an enzymatic lignin graphite phase carbon nitride composite material. The synthetic material has strong mechanical properties and chemical stability, and has abundant zinc-affinity active sites, which can induce uniform deposition of zinc ions and inhibit dendrite reactions; the active groups contained in the composite material can react with H in the electrolyte. + The formation of hydrogen bonds can inhibit the occurrence of zinc negative electrode side reactions and hydrogen evolution reactions, thereby increasing the cycle life of zinc batteries.

[0018] (2) The present invention uses the synthesized enzymatically hydrolyzed lignin graphite phase carbon nitride composite material as a coating material in an aqueous zinc ion battery, which can effectively inhibit the corrosion of the electrolyte on the zinc negative electrode and improve the cycle stability of the aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The contact angle diagrams are shown for MCN@Zn prepared in Example 1 (as shown in FIG. b) and Bare Zn prepared in Comparative Example 1 (as shown in FIG. a).

[0020] Figure 2 Impedance diagram of the symmetrical battery of MCN@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1.

[0021] Figure 3 The cyclic charge and discharge diagrams of the half-cells of MCN@Zn prepared in Example 1 and Bare Zn prepared in Comparative Example 1.

[0022] Figure 4 The cyclic charge and discharge diagrams of the half-cells of MCN@Zn prepared in Example 1 and g-C3N4@Zn prepared in Comparative Example 3.

[0023] Figure 5 The cyclic charge and discharge diagrams of the half-cells of MCN@Zn prepared in Example 1 and M@Zn prepared in Comparative Example 2.

[0024] Figure 6 This is a comparison chart of the coating morphologies of MCN@Zn prepared in Example 1 and MCN@Zn-1 prepared in Comparative Example 4. DETAILED DESCRIPTION

[0025] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0026] Example 1

[0027] (1) Urea was placed in a crucible with a lid, and subjected to heat treatment in a muffle furnace, with a heating rate of 4.6°C / min for 2 hours to 550°C, and calcined at 550°C for 2 hours to obtain a light yellow solid, which was ground into powder to obtain a light yellow solid powder named g-C3N4;

[0028] (2) g-C3N4, enzymatic lignin and polyvinylidene fluoride (PVDF) were ball-milled in a mass ratio of 5:1:1, 5-7 drops of N-methylpyrrolidone (NMP) were added and stirred until it became a coating state, and the coating was coated on zinc foil using a coating machine to prepare a zinc negative electrode material. The prepared zinc negative electrode material was named MCN@Zn.

[0029] Comparative Example 1

[0030] The metal zinc foil was not treated and was named Bare Zn.

[0031] Comparative Example 2

[0032] (1) Enzymatically hydrolyzed lignin and polyvinylidene fluoride (PVDF) were ball-milled in a mass ratio of 5:1, 5-7 drops of N-methylpyrrolidone (NMP) were added and stirred until the mixture became a coating state, and the coating was coated on zinc foil using a coating machine to prepare a zinc negative electrode material. The prepared zinc negative electrode material was named M@Zn.

[0033] Comparative Example 3

[0034] (1) Urea was placed in a crucible with a lid, and subjected to heat treatment in a muffle furnace, with a heating rate of 4.6°C / min for 2 hours to 550°C, and calcined at 550°C for 2 hours to obtain a light yellow solid, which was ground into powder to obtain a light yellow solid powder named g-C3N4;

[0035] (2) g-C3N4 and polyvinylidene fluoride (PVDF) were ball-milled in a mass ratio of 5:1, 5-7 drops of N-methylpyrrolidone (NMP) were added and stirred until it became a coating state, and the coating was coated on zinc foil using a coating machine to prepare a zinc negative electrode material. The prepared zinc negative electrode material was named g-C3N4@Zn.

[0036] Comparative Example 4

[0037] (1) Urea was placed in a crucible with a lid, and subjected to heat treatment in a muffle furnace, with a heating rate of 4.6°C / min for 2 hours to 550°C, and calcined at 550°C for 2 hours to obtain a light yellow solid, which was ground into powder to obtain a light yellow solid powder named g-C3N4;

[0038] (2) g-C3N4, enzymatic lignin and polyvinylidene fluoride (PVDF) were ball-milled in a mass ratio of 1:1:1, 5-7 drops of N-methylpyrrolidone (NMP) were added and stirred until it became a coating state, and the coating was coated on zinc foil using a coating machine to prepare a zinc negative electrode material. The prepared zinc negative electrode material was named MCN@Zn-1.

[0039] Application Example 1

[0040] The MCN@Zn prepared in Example 1 was used as the negative electrode and the copper foil was used as the positive electrode. The two were assembled into a half-cell, wherein the electrolyte was a 2 mol / L zinc sulfate solution for charge and discharge cycle testing.

[0041] Test method: At a current density of 5 mA cm -2 、Capacity cutoff 1mAh·cm -2 The half-cell test was carried out under experimental conditions.

[0042] Test results:

[0043] like Figure 1 The contact angle of MCN@Zn prepared in Example 1 is greater than that of Bare Zn prepared in Comparative Example 1. This material is a hydrophobic material and can effectively isolate the corrosion of the zinc negative electrode surface by the aqueous electrolyte.

[0044] like Figure 2 : The impedance of MCN@Zn prepared in Example 1 is lower than that of Bare Zn prepared in Comparative Example 1.

[0045] like Figure 3 The CE of the MCN@Zn half-cell prepared in Example 1 remained at a relatively high efficiency after 430 charge-discharge cycles, while the Bare Zn half-cell prepared in Comparative Example 1 short-circuited after 46 charge-discharge cycles.

[0046] like Figure 6 (a): The MCN@Zn prepared in Example 1 has good coating effect, uniform distribution and smooth surface. Graphite phase carbon nitride as a carrier material is conducive to the enzymatic hydrolysis of lignin to form a coating on the surface of zinc foil, and it has high mechanical strength, isolating the aqueous electrolyte from corroding the zinc negative electrode surface.

[0047] Application Comparative Example 1

[0048] The Bare Zn prepared in Comparative Example 1 was used as the negative electrode and the copper foil was used as the positive electrode. The two were assembled into a half-cell, wherein the electrolyte was a 2 mol / L zinc sulfate solution for charge and discharge cycle testing.

[0049] Test method: At a current density of 5 mA cm -2 、Capacity cutoff 1mAh·cm -2The half-cell test was carried out under experimental conditions.

[0050] Test results:

[0051] like Figure 2 : The impedance of the Bare Zn symmetric battery prepared in Comparative Example 1 reaches 786.

[0052] like Figure 3 : The Bare Zn half-cell prepared in Comparative Example 1 short-circuited after 46 cycles of charge and discharge.

[0053] Application Comparative Example 2

[0054] The M@Zn prepared in Comparative Example 2 was used as the negative electrode and the copper foil was used as the positive electrode. The two were assembled into a half-cell, in which a 2 mol / L zinc sulfate solution was used as the electrolyte for charge and discharge cycle testing.

[0055] Test method: At a current density of 5 mA cm -2 、Capacity cutoff 1mAh·cm -2 The half-cell test was carried out under experimental conditions.

[0056] Test results:

[0057] like Figure 5 The CE of the MCN@Zn half-cell prepared in Example 1 remained at a relatively high efficiency after 430 charge and discharge cycles, while the M@Zn half-cell prepared in Comparative Example 2 short-circuited after 210 charge and discharge cycles.

[0058] Application Comparative Example 3

[0059] The g-C3N4@Zn prepared in Comparative Example 1 was used as the negative electrode and the copper foil as the positive electrode, and the two were assembled into a half-cell, in which a 2 mol / L zinc sulfate solution was used as the electrolyte for charge and discharge cycle testing.

[0060] Test method: At a current density of 5 mA cm -2 、Capacity cutoff 1mAh·cm -2 The half-cell test was carried out under experimental conditions.

[0061] Test results:

[0062] like Figure 4 : The half-cell of MCN@Zn prepared in Example 1 maintained a high CE efficiency after 430 charge and discharge cycles, while the half-cell of g-C3N4@Zn prepared in Comparative Example 3 short-circuited after 150 charge and discharge cycles.

[0063] Application Comparative Example 4

[0064] The MCN@Zn-1 prepared in Comparative Example 1 was used as the negative electrode and the copper foil was used as the positive electrode. The two were assembled into a half-cell, in which a 2 mol / L zinc sulfate solution was used as the electrolyte for charge and discharge cycle testing.

[0065] Test method: At a current density of 5 mA cm -2 、Capacity cutoff 1mAh·cm -2 The half-cell test was carried out under experimental conditions.

[0066] Test results:

[0067] like Figure 6 (b): MCN@Zn-1 prepared in Comparative Example 4 cannot form a coating on the surface of zinc foil.

[0068] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a negative electrode coating material for an aqueous zinc ion battery, characterized in that: The following steps are involved: (1) Using urea as a raw material, a light yellow solid powder is obtained by heat treatment; (2) Light yellow solid powder, enzymatic lignin and polyvinylidene fluoride are ball-milled and mixed according to a mass ratio, and N-methylpyrrolidone is added dropwise and stirred until the mixture becomes a coating state; thereby obtaining a negative electrode coating material.

2. The method for preparing a negative electrode coating material for an aqueous zinc ion battery as claimed in claim 1, wherein: In step (1), urea is placed in a crucible and heat treated in a muffle furnace. The heat treatment conditions are: heating rate 4-5°C / min, calcination temperature 500-600°C, and calcination time 2-3 hours.

3. The method for preparing a negative electrode coating material for an aqueous zinc ion battery as claimed in claim 1, wherein: Step (2) Graphite phase carbon nitride, enzymatic lignin and polyvinylidene fluoride are mixed in a mass ratio of 1-5:1:1, ball milled at a speed of 600-650 r / min, for 30-60 min, and 5-7 drops of N-methylpyrrolidone are added.

4. The method for preparing a negative electrode coating material for an aqueous zinc ion battery as claimed in claim 1, wherein: In step (1), urea is placed in a crucible and heat treated in a muffle furnace. The heat treatment conditions are: heating rate 4.6°C / min, calcination temperature 550°C, and calcination time 2 hours.

5. The method for preparing a negative electrode coating material for an aqueous zinc ion battery as claimed in claim 1, wherein: Step (2) Graphite phase carbon nitride, enzymatically hydrolyzed lignin and polyvinylidene fluoride are mixed in a mass ratio of 5:1:1 and ball milled for 30 minutes.

6. Application of the negative electrode coating material prepared by the preparation method according to any one of claims 1 to 5 in the preparation of zinc negative electrode materials.

7. The use according to claim 6, characterized in that: The coating material is coated on the zinc foil by a coating machine to prepare the zinc negative electrode material.

Citation Information

Patent Citations

  • Graphite-phase carbon nitride composite material and preparation method and application thereof

    CN111957335A

  • Supramolecular induced nitrogen-doped lignin derived carbon material as well as preparation method and application thereof

    CN115215320A